O limite legal do percentual da despesa com pessoal face à proximidade das eleições e à contratação de pessoal terceirizado –um estudo empírico para os municípios cearenses –2007 a 2016 - Mota, Janaína Silveira (2018)
The efficient allocation of public resources is one of the greatest challenges for managers. This difficulty is observed more forcefully at the municipal level, since such entities have a high degree of dependence on transfers from States and Federal Government. In addition, the Fiscal Responsibility Law established to the municipalities a limit for the commitment of revenue with salaries expenses to 60% of Net Current Revenue, which, if not respected, entails restrictions to administration. In this context, the objective of this study was to verify if an eventual economic crisis would have caused a decrease of the transfers from State and Federal Government, and if it would cause a raise of the percentage of revenue with salaries without increase, in fact, the value of the expenses; also verify the behavior of the revenue with salaries expenses and the cost of contracting outsourced services with the approaching of the elections; the degree of commitment of salaries expenses affects the cost of contracting outsourced services (individuals and legal entities) not considered in salaries expenses, in order to test the possibility of this item being used as a way to circumvent the legal limit. The data is provided by the municipalities of Ceará to the former Court of Audit of the Municipalities of the State of Ceará (TCM/CE), related to the interstices from 2007 to 2016. Among the results obtained, it was verified that the transfers received for the municipalities didn’t decrease, so that wasn’t the cause of the raise of the percentage of the salaries expenses. It was verified that, as expected, the salaries expenses increase as long as the elections approach; the same was concluded about expenses specific with executive branch. However, different from initial suspect, the cost of contracting outsourcing services decrease as long as the elections approach.